Membangun Citra Pariwisata Kota Batam Melalui Analisis Konten Instagram @Batampromotion - Lubis, Yomi Shela Raihan; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2023)
@batampromotion is a promotional information media in Batam on Instagram which had trusted by public to share information about tourism, property, automotive, culinary, and others in Batam. @batampromotion is quite active to updating content on Instagram that makes Instagram’s user interested to follow. @batampromotion is one of the accounts that having a prominent profile on Instagram, as a content creator who creates things that interest the public according to trending topics. The purpose of this research is to find out how @batampromotion’s Instagram builds the tourism image of Batam by content analysis. This research is a qualitative research using a descriptive method of content analysis approach with the object of research is content on @batampromotion’s Instagram. The results of the research is @batampromotion is uses a communication strategy through New Media Instagram by focusing on the quality of an interesting content and a relaxed manner of communication so that is easily to be understood by followers and/or other Instagram’s users. An image that built through @batampromotion’s Instagram content, Batam is described as a tourism city that focuses on entertainment places. The form of communication used is verbal communication which makes it easier for followers to receive more detailed information by adding textual explanations to the content.